Pembacaan Non-Homofobik Terhadap Ayat-ayat Sejarah Homoseksualitas Dalam Alquran: Menuju Penafsiran Sensitif-Seksualitas - Muhammad Dluha Lutfillah (UIN Siber Syekh Nurjati Cirebon, 2018)
The Muslim understanding of the Qur'anic verses about the history of homosexuality particularly the phrase maÂ sabaqakum bihaÂ min ahad min al-'alamin for centuries reads that no man before your people the prophets Lutâ€™s people, more than 20th BCÂ who ever took action fakhisha ' which is then interpreted by the so-called' neo-orthodox 'as homosexuality. This understanding is in the contrary with the results result of an Egyptologist Greg Reeder saying that the first possible homosexual couple were Niankhkhnum and Khnumhotep, two manicurists at the age of the Fifth Dynasty of the Kingdom of Ancient Egypt (more than 25th BC). The contradiction then inspects a man on the question of â€œWhether Qur'an incorrectly cite the history?â€ Suspicion is suspended by al-Razi which provides a more accommodative alternative to the Reeder study, which is 'beyond what you do in it' which gives the possibility of a group of people who did homosexuality in the past 20 BC.Â Â